Heat transfer enhancement by chaotic advection in a novel sine-helical channel geometry. (1st September 2022) - Aldor, Abbas; Moguen, Yann; El Omari, Kamal; Habchi, Charbel; Cocquet, Pierre-Henri; Le Guer, Yves
Highlights: An innovative sine-helical heat exchanger based on chaotic advection was introduced and studied. The performance of the chaotic heat exchanger was analyzed numerically in the laminar regime and compared to a helical one. The results showed that chaotic advection enhanced the mixing and heat transfer inside the sine-helical channel. The thermal enhancement factor increased between 5.5 and 20.7% in the since-helical channel relative to the helical channel. Graphical abstract: Abstract: In this paper, we present an innovative sine-helical heat exchanger whose channel geometry consists in a combination of a helically coiled geometry and a sine-wave geometry. Laminar flow is considered in the present study, with the Reynolds numbers ranging from 100 to 1400 based on the hydraulic duameter and mean flow velocity. The flow structure and the convective heat transfer in the novel heat exchanger are analyzed numerically using the finite volume method. The results are compared to those obtained with a classical helically coiled heat exchanger. It is shown that the periodic change of the centrifugal forces in the sine-helical channel breaks the flow symmetry and leads to chaotic particle trajectories. The effect of chaotic advection on the enhancement of mixing efficiency is proven. The coefficient of variation of the outlet temperature in the sine-helical flow is decreased by about 100% relative to that in the helical channel, highlighting thus a better temperature homogeneity. Moreover, the thermal enhancement factor, measuring the convective heat transfer coefficient at same pumping power, increases between 5.5 and 20.7% in the since-helical flow relative to the helical channel. Consequently, the proposed novel heat exchanger is very promising for many applications with laminar flow regimes.